Maintaining the Standards of Competence for Hydrographic Surveyors and Nautical Cartographers: A Modern Approach - Miller, Keith; Armstrong, Andy; Furness, Ron; Greenland, Adam; Johnston, Gordon; Nairn, Rod; Roscher, Nickolas; Seube, Nicolas; Syawie, Sobri; Tsoulos, Lysandros (The International Hydrographic Review, 2017)
The International Board on Standards of Competence for Hydrographic Surveyors and Nautical Cartographers maintains standards in these disciplines and awards recognition to programs of education found to be compliant. Standards have been fully revised and updated, both in terms of expectations of stakeholders and in nomenclature used in education. This paper provides the rationale behind the new format adopted for presentation of the standards and offers information useful to institutions in development of programs with the intention of gaining recognition. In the broader scope of education, the principles adopted in development of the standards offer a novel approach; expressing core requirements in professional education and training while allowing flexibility for further specialization.